2013
DOI: 10.1111/imr.12072
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal immunology of HIV infection

Abstract: Summary Recent advances in the immunology, pathogenesis, and prevention of human immunodeficiency virus (HIV) infection continue to reveal clues to the mechanisms involved in the progressive immunodeficiency attributed to infection but more importantly have shed light on the correlates of immunity to infection and disease progression. HIV selectively infects, eliminates, and/or dysregulates several key cells of the human immune system, thwarting multiple arms of the host immune response, and inflicting severe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
58
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 270 publications
(394 reference statements)
1
58
0
Order By: Relevance
“…7 In the gastrointestinal tract, infected macrophages induce severe damages to mucosal barriers, resulting in translocation of others pathogens, a hallmark of HIV-1 infection. [9][10][11] Therefore, control of tissue infiltration of HIV-infected macrophages represents a therapeutic challenge. 7,9,12 Although there are no studies investigating whether macrophage migration is modified on HIV-1 infection, several reports have addressed this issue in infected CD4…”
Section: Introductionmentioning
confidence: 99%
“…7 In the gastrointestinal tract, infected macrophages induce severe damages to mucosal barriers, resulting in translocation of others pathogens, a hallmark of HIV-1 infection. [9][10][11] Therefore, control of tissue infiltration of HIV-infected macrophages represents a therapeutic challenge. 7,9,12 Although there are no studies investigating whether macrophage migration is modified on HIV-1 infection, several reports have addressed this issue in infected CD4…”
Section: Introductionmentioning
confidence: 99%
“…Studies in this model system have identified resting vaginal CD4+ T cells expressing CCR5 (▶ HIV-1 Transmission; Association with Host Genotypes) but negative for activation markers HLA-DR and Ki67, as early targets for infection (Haase 2011). The susceptibility of vaginal CD4+ T cells to infection is also illustrated by the rapid depletion of these cells following intravenous exposure to SIV (Xu et al 2013).…”
mentioning
confidence: 98%
“…These studies suggest that both cell-free and cell-associated virions can successfully establish infection through the female reproductive tract. The precise events that allow HIV-1 to traverse the genital epithelium remain controversial but may include transcytosis across intact epithelial cells; transport through gaps between epithelial cells, or through breaches in the epithelial layer; binding and uptake by Langerhans cells in the genital epithelium, followed by transfer of virion particles to T cells; and direct infection of intraepithelial CD4+ T cells (Hladik and McElrath 2008;Xu et al 2013; Fig. 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Various mucosal target cells including antigen-presenting cells (APCs) such as Langerhans cells (LCs), interstitial dendritic cells (iDCs), or plasmacytoid dendritic cells have the capacity to capture antigen, to migrate to draining lymph nodes, and to transfer HIV to surrounding memory CD4 + T cells. [4][5][6][7] Dendritic cells (DCs) play a critical role in HIV transmission by transporting infectious HIV virions without being infected themselves (transfer in trans) or by transferring newly synthesized virus (transfer in cis).…”
mentioning
confidence: 99%